Analisis Potensi Kejadian Medication Errors pada Fase Prescribing dalam Pelayanan Resep Pasien Rawat Jalan di Rumah Sakit Bhayangkara Brimob: Analysis of the Potential Incidence of Medication Errors in the Prescribing Phases in Outpatient Prescription Services at Bhayangkara Brimob Hospital - Septi Tri Astuti; Eka Pebi Hartianty; Rahayu Wijayanti (Universitas Gunadarma, 2025)
Prescription assessment is an activity that plays an important role in ensuring appropriate drug use and preventing medication errors. Medication errors most often occur in the prescribing phases, which is medication errors that occur during drug prescribing. This study aims to determine the implementation of prescription assessment and the potential incidence of medication errors in the prescribing phase in the assessment of outpatient prescriptions at Hospital Bhayangkara Brimob. The type of research used in this study is non-experimental research using descriptive research methods with retrospective data collection for the period October – December 2023. Sampling was the techniques of purposive sampling and calculated using the slovin formula so as to get minimum sample of 395 prescriptions and the number of samples used in this study was 450 prescriptions. The results showed that there was a potential for medication errors in the prescribing phase based on pharmaceutical and clinical requirements. In pharmaceutical requirements, it was found that the name, form or dosage strength of the drug was no listed by 14% (63 prescriptions), inapproopriate drug dosage by 25,33% (114 prescriptions), and inappropriate use rules by 20% (90 prescriptions). In clinical requirements, duplication of drugs was found at 1,11% (5 prescriptions) and drug interactions at 20,22% (91 prescriptions). Meanwhile, administrative requirements did not identify any potential medication errors. The conclusion of this study is that outpatient prescriptions at Bhayangkara Brimob Hospital still have the potential for medication errors in the prescribing phase based on pharmaceutical and clinical requirements.